Spatiotemporal regulation of the GPCR activity of BAI3 by C1qL4 and Stabilin-2 controls myoblast fusion. Issue 1 (December 2018) - Hamoud, Noumeira; Tran, Viviane; Aimi, Takahiro; Kakegawa, Wataru; Lahaie, Sylvie; Thibault, Marie-Pier; Pelletier, Ariane; Wong, G.; Kim, In-San; Kania, Artur; Yuzaki, Michisuke; Bouvier, Michel; et al.
Abstract Myoblast fusion is tightly regulated during development and regeneration of muscle fibers. BAI3 is a receptor that orchestrates myoblast fusion via Elmo/Dock1 signaling, but the mechanisms regulating its activity remain elusive. Here we report that mice lacking BAI3 display small muscle fibers and inefficient muscle regeneration after cardiotoxin-induced injury. We describe two proteins that repress or activate BAI3 in muscle progenitors. We find that the secreted C1q-like1–4 proteins repress fusion by specifically interacting with BAI3. Using a proteomic approach, we identify Stabilin-2 as a protein that interacts with BAI3 and stimulates its fusion promoting activity. We demonstrate that Stabilin-2 activates the GPCR activity of BAI3. The resulting activated heterotrimeric G-proteins contribute to the initial recruitment of Elmo proteins to the membrane, which are then stabilized on BAI3 through a direct interaction. Collectively, our results demonstrate that the activity of BAI3 is spatiotemporally regulated by C1qL4 and Stabilin-2 during myoblast fusion. Myoblast fusion is an essential step in muscle growth and regeneration, and is regulated by the G-protein coupled receptor (GPCR) BAI3. Here Hamoud et al. show that the GPCR activity of BAI3 is spatiotemporally regulated during myoblast fusion, and identify C1qL4 and Stabilin-2 as, respectively, negative and positive regulators of its activity.